تحديد الكفاءة الحرارية الأمثل لنموذج مركز شمسي خطي قطعي - عيسى مراد; براءه حمادي (Tishreen University, 2017)
إنَّ ازدياد الطلب على الطاقة والمشاكل الناجمة عن تلوث البيئة أدى إلى التوجه لرفع كفاءة استخدام الطاقة من خلال الأبحاث العلمية المرتبطة بالطاقات المتجددة. خاصة أنَّ سورية تتمتع بإشعاع شمسي عالي وزمن سطوع شمسي طويل. يتركز البحث حول تحديد الكفاءة الحرارية لنموذج مركز شمسي خطي قطعي (PTC) بهدف الحصول على النموذج الأمثل حرارياً واقتصادياً وفق الشروط المناخية لمدينة دمشق. تم وضع نموذج رياضي للمركز المدروس وفق الأبعاد التصميمية المحسوبة من خلال حل معادلات الزوايا الشمسية والإشعاع الشمسي المباشر على مدار السنة. وقد تم حل هذا النموذج باستخدام عدة برامج حاسوبية (Excel, EES). بينت النتائج أنَّ زيادة زاوية الحافة تؤدي إلى زيادة كفاءة المركز, وإنَّ أفضل كفاءة للمركز حرارياً واقتصادياً بلغت ( ) عند زاوية حافة ( ). وتكون الأبعاد التصميمية لنموذج المركز هي: (S= 3.66 [m], Wa= 3.56, , rr= 2.15 [m]) لأجل تدفق 0.61 [kg/s] ودرجة حرارة تصميمية 85 [ͦ C] لمائع نقل الحرارة )الماء( عند قطر خارجي للمستقبل . The drastically increase in energy demand and the problems resulted from environmental pollution have led to a serious trend towards energy utilization efficiency improvement through scientific researches related to renewable energies, particularity that Syria has a high solar irradiance and prolonged sunshine hours. This research focuses on determining the thermal efficiency for a prototype of a parabolic trough solar concentrator (PTC) to obtain the optimal prototype thermally and economically according to climatic conditions in Damascus. It has been deposited the mathematical model of the studied concentrator depending on the calculated design parameters through calculating the solar angles equations and direct solar irradiance throughout the year. And it has been solved this model by using numerous computer programs (Excel, EES). The results showed that the increasing of rim angle lead to increasing the thermal efficiency of the concentrator and the preferable efficiency of the concentrator thermally and economically reached ( ) at rim angle ( ). And the design parameters of the concentrator prototype are (S= 3.66 [m], Wa= 3.56, , rr= 2.15 [m]) for mass flow rate 0.61 [kg/s] and design temperature 85 [ºC] of heat transfer fluid (water) at the outer diameter of the receiver .